The need to improve the personnel training system for public security activities of internal affairs bodies (Eurasian Journal of History, Geography and Economics, 2023)
The article describes the analysis of the experience of some foreign countries in the training of personnel for the public security service of internal affairs bodies (police) and the ways of improving the system of training personnel for the activities of public security of internal affairs bodies in Uzbekistan.